ENHANCEMENT OF PROBLEM-SOLVING SKILL USING IDEAL PROBLEM-SOLVING LEARNING MODEL - Syarifatul Luthfia (SUJANA: Education and Learning Review, 2023)
The requirements of 21st century student competencies are getting more complex. One of the skills that must be developed is problem solving skills. The objective of this research is improving problem-solving skills in electricity through IDEAL problem-solving skills. There are five steps in IDEAL, which are (1) identify the problem; (2) define the goal; (3) explore possible solutions, ideas, or strategies; (4) anticipate results and act; and (5) review and learn. The results of the midterm exam in science subjects for the sixth grade of Al-Irsyad elementary school are low. Based on the research results, it indicates that students’ problem solving must be improved. There are 11 students at the insufficient level, 6 students at the sufficient level, 6 students at the good level, and 2 students at the excellent level. This research method used classroom action research. Classroom action research consists of four steps, which are planning, action, observation, and reflection. This research consisted of two cycles. The class average in the first cycle was 85.28. There were 5 students at the less level, 8 students at the sufficient level, 2 students at the good level, and 10 students at the excellent level. The class average in the second cycle was 85.36. There were 5 students at the poor and fair level, 2 students at the good level, and 13 students at the excellent level. The class average was 85.36 and better than the first cycle about 0.6. Therefore, it means that the IDEAL problem solving model is effective in improving students’ problem solving skills.